A Circumcision as a Manifestation of Violation of the Right to Free Personality Development - Márquez García, Elda Yasmín; García Carvajal, Javier Alfonso (DIXI, 2014)
Ths article is the result of a research project completed by the authors in 2012. It focused on the analysis of regulatory, legal and doctrinal evolution of the right to free personality development aimed at protecting the right of children to decide about their bodies and what they want to become as adults. Th elaboration of a jurisprudence line of the Colombian Constitutional Court is used as a research tool based on the methodology proposed in the book . “The Right of the Judges” by professor Diego López. Once the effcts of the State, the family and the society on the violation of the right to free personality development in children are identifid, the responsibility of each of them is measured according to political, legal, moral, medical and social criteria and the responsibility of the State. Thn, ways of violating the right to free personality development are presented in this article that concludes presenting the reasons through which circumcision could constitute one of them.